Negotiating identities through the ‘cultural practice’ of labia elongation among urban Shona women and men in contemporary Zimbabwe - Venganai, Hellen (My University, 2017)
Dominant Eurocentric discourses on African traditional cultural practices linked to sexuality construct these practices as retrogressive for women in these localities. These discourses take the form of women and sexual rights promoted by some women activists and scholars, whose work mainly focuses on the so-called traditional rural women as victims of these gendered sexual practices. In many ways, such approaches manufacture and exaggerate differences between Western and African women, while reproducing colonial discourses that construct Africans as backward. This article interrogates the modern-traditional binary which underpin conventional representations of some sexual practices as cultural. Following African feminist scholars who argue for research which explores the significance and meanings such sexual practices hold for those women who engage in them, this article draws on a study I conducted with Shona speaking women and men in Zimbabwe who participated and/or were interested in the practice of labia elongation. The targeted women and men, in their 20s -30s, live in relatively affluent houses in Harare, and are identified as urban, modern and middle-class. The study sought to explore why such women (as well as men) who identify as modern were so interested and invested in a sexual practice that has often been constructed as traditional and cultural. By exploring how women and men invoke notions of culture and tradition, the article demonstrates the creative and complex ways in which the young adults position themselves in relation to this practice in particular, and in relation to gender and sexuality more generally.
Keywords: 306 Kultur und Institutionen; Labia elongation; Shona women; sexuality; identities; culture; Zimbabwe